DISEASES OF THE DIGESTIVE ORGANS OF EQUINES (Лучшие интеллектуальные исследования, 2025)
Abstract: This in the article of horses digestion to do diseases, their causes, symptoms and treatment methods about in detail information Colic, gastritis, stomach​​ ulcers, intestines parasites​ and stomach ache​ such as of diseases etiology and clinical appearances analysis This is also​​ of diseases prevent to take according to important recommendations given. Article horses health save them​ food in order attention to give and preventive measures done increase according to useful information own inside This​​ research horse breeders, veterinarians and horse to care interested parties for important source become service does.